Presentation of Self on Facebook - Milani, Raheleh Sadeghzadeh (2010)
In recent years, Facebook has erupted as a phenomenon in a variety of contexts. It is quickly becoming a significant topic in academia, where there is a varied and quickly growing body of literature in a number of fields. Facebook has been rapidly adopted by users who use it to maintain existing relationships and also as a medium in which to present themselves through their profiles information. This research aims to explore how much users present themselves on Facebook and the impressions they want others to form of them when looking at their profiles. To examine the types of self-presentation displayed in Facebook profiles, this study uses the self-presentation theory (Goffman, 1959). The questionnaire survey was employed as the instrument for data collection in this study. The results revealed that the level of self-presentational behaviors to be moderate and the level of expected impressions from Facebook friends for most of the respondents was not high. Additionally, the findings indicated that there was a significant difference for expected impressions from Facebook friends among different races. The study also showed that the extent of information Facebook users self-disclose was moderate. It can be concluded that respondents have moderately self-presented through Facebook by changing their profile pictures, leaving comments, writing on their ontacts' "walls", as well as "lik(ing)" their contacts' posts. In addition, in spite of respondents' “low” level of expectancy, they were active in publishing their 'selves' in forms of pictures as well as sharing special links/videos/ texts. Furthermore, based on this study, self-presentation in form of information exaggeration is not independent of race.